Religiosidad popular en el reino de Granada, España (ss. XIII–XV): Sufismo y rábitas en la Alpujarra - Trillo San José, Carmen (Studia Orientalia Electronica, 2016)
This paper analyses popular religiouness and the rábitas in the Alpujarra, a rural area on the southern slopes of Sierra Nevada, during the Nasrid reign of Granada (XIII-XV centuries). It was the last Muslim area in Spain to be conquered by the Crown of Castile. At that time, Sufism flourished in the kingdom of Granada and particularly in the Alpujarra, as evinced by the Sufi Abū Marwān al-Yuḥānisī. We further study some popular religious manifestations related to this spiritual tendency, such as the rábitas, the celebration of the birth of the Prophet, or Mawlid, and the veneration of tombs. To this end, we use an unpublished document, the books of waqfs (pious endowments) of the year 1501, a date immediately following the conversion of the Mudejares to Christianity. The rábitas were not only religious but also social and geographical elements of great importance in the villages (alquerías) of the Alpujarra. The rábitas were at the heart of neighbourhoods and in the villages but also in the outskirts, marking their boundaries. They were linked to the local people of each neighbourhood as an emblematic element. They were also connected to certain family groups. The books of waqfs, often shared with the mosques, show that the local people valued both institutions. Despite the historical rivalry between Sufism and politicians and the politico-judiciary, in this region we have not found any evidence of conflict between the mosques and the rábitas. Hence we can state that in popular religiousness there was no confrontation between the official religion and the mystic tendencies in this rural area. KEYWORDS: Middle Ages, Nasrid kingdom of Granada, Sufism, rábitas.